Analisis Antrian dengan Model Single Channel Single Phase: Studi Kasus Supermarket Ngagel - Dhae, Lusialapin Dolfna; Aquilan, Delvina Jesslyn; Deviyanti, I Gusti Ayu Sri; Yuliana, Pram Eliyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Food stands at the Ngagel Supermarket shopping center, Surabaya, often experience long queues, especially during peak hours, which can reduce customer comfort. This research aims to analyze the queuing system using a single channel single phase model in order to evaluate service performance and provide recommendations for improvement. The method used is a descriptive quantitative approach with direct observation to collect data on arrival and customer service. The analysis results show that the level of service intensity (ρ) is 0.7, the average number of customers in the system (L) is 2.33 customers, and the average number of customers waiting in line (Lq) is 1.63 customers. Meanwhile, the average customer time in the system (W) is 3.33 minutes and the average time waiting in line (Wq) is 2.34 minutes. These findings suggest that even if the system is running fairly efficiently, increasing customer volumes can cause queues to build up. Therefore, it is recommended that there be additional service points or better queue management to maintain service efficiency and comfort.